Spectroscopic, electrochemical and computational studies of rhenium(I) and ruthenium(II) complexes incorporating the novel tetradentate ligand 1,4-bis(4-(4'-methyl)-2,2'-bipyridyl)-2,3-diaza-1,3-butadiene (BBDB) and its derivatives - Cattaneo, Mauricio (2014)
The novel tetradentate ligand 1,4-bis(4-(40-methyl)-2,20-bipyridyl)-2,3-diaza-1,3-butadiene (BBDB) was synthesized and characterized by spectroscopic techniques. New complexes of Re and Ru of formulae: [Re(BBDB)(CO)3(Cl)], [(CH3CN)(CO)3Re(l-BBDB)Re-(CO)3(CH3CN)]2+, [(bpy)2Ru-(l-BBDB)Ru(bpy)2]4+, [(NH3)4Ru(l-BBDB)?Ru(NH3)4]4+ (bpy = 2,20-bipyridine) and complexes of Ru with 4-Me-40-CO2H-bpy (=4-methyl-40-carboxylic acid-2,20-bipyridine) - the hydrolyzed derivative of BBDB- of formulae: [(Ru(4-Me-40-CO2H-bpy)(bpy)2]2+ and [Ru(4-Me-40-CO2H-bpy)(CN)4]2 were prepared and characterized by spectroscopic, electrochemical and computational techniques. The disclosed enhanced electronic coupling in the mixed-valent complex with ruthenium ammines can be explained by the electronic delocalization imposed by the -C=N-N=C- backbone. DFT and TD-DFT calculations can predict the optical properties and electronic structures of the reported complexes and comparisons with calculations performed on previously reported complexes with 4-pyridinaldazine can account for their photophysical behaviour.